2013
DOI: 10.1177/1066480713476848
|View full text |Cite
|
Sign up to set email alerts
|

Recollected Parental Care and Fear of Intimacy in Emerging Adults

Abstract: Two samples of university students (combined N= 299; mean age = 24.97; 86% female) completed the care subscale of the parental bonding instrument and the Fear of Intimacy scale. Analyses indicated that recollected parental care and fear of intimacy were negatively correlated. Concurrently, it was found that (1) participants who reported having a warm, caring relationship with at least one parent were significantly less likely to suffer from a fear of intimacy and (2) participants who scored low on the measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Thus, it appears that the association between adults’ remembrances of parental rejection in childhood—as partially mediated by adults’ psychological maladjustment and relationship anxiety—is stable across cultures and genders. These results are consistent with conclusions drawn by Phillips et al (2013) who found that adults’ recollections of parental care (acceptance) in childhood were negatively correlated with fear of intimacy in adulthood.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, it appears that the association between adults’ remembrances of parental rejection in childhood—as partially mediated by adults’ psychological maladjustment and relationship anxiety—is stable across cultures and genders. These results are consistent with conclusions drawn by Phillips et al (2013) who found that adults’ recollections of parental care (acceptance) in childhood were negatively correlated with fear of intimacy in adulthood.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the work of Phillips et al (2013) comes closer than the work of Repić (2007) or Espeleta et al (2017) to matching IPARTheory’s expectations about the relation between childhood rejection and adult fear of intimacy. In that study, Phillips et al (2013) reported that recalled parental care (acceptance) in childhood was negatively correlated with fear of intimacy in a sample of young adults. That is, individuals who reported having a warm, caring relationship with at least one parent (especially mothers) in childhood were significantly less likely to develop a fear of intimacy than were those adults who did not have such a relationship.…”
mentioning
confidence: 90%
“…In another study, researchers administered the Parental Bonding Instrument (Parker et al, 1979) and the Fear of Intimacy Scale (FIS; Descutner & Thelen, 1991) to a sample of university students from the United States (Phillips et al, 2013). Recalled parental care in childhood was negatively and weakly correlated with adults’ FOI.…”
Section: The Consequences Of Interpersonal Relationshipsmentioning
confidence: 99%
“…In addition, rejected children and adults often construct mental images of personal relationships as being unpredictable, untrustworthy, and hurtful (Zimmer‐Gembeck et al, ). In new relationships, these negative mental representations make it difficult for rejected individuals to trust others emotionally (Phillips et al, ). They are also likely to become hypervigilant and hypersensitive, and to overreact to any slights or signs of emotional undependability.…”
Section: The Subtheories Of Ipartheorymentioning
confidence: 99%